Populism and Social Polarization in European Democracies - Victor Ginsburgh; Sergio Perelman; Pierre Pestieau (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The objective of this paper is to explain populist attitudes that are prevailing in a number of European democracies. Populist attitudes expectedly lead to social protests and populist votes. We capture the populist wave by relying not on voting behavior but rather on values that are traditionally viewed as populist values, such as distrust of institutions and neighbors, rejection of migrations and strong preferences for law and order. Our study covers the period 2004 to 2018 and 25 European countries for which we match aggregated indicators of populist values and social polarization computed from ESS and SILC survey micro-data, respectively. We find that social polarization, along with other factors, can explain populist attitudes. We also observe that both populist attitudes and polarization vary across countries much more than over time, with the exception of authoritarian values which appear positively correlated with social polarization, particularly among baby-boomers and younger cohorts.
Keywords: D63; I30; 330; populism; polarization; social divide